Factors that influence WAQF creation in Malaysia - Tahirah Abdullah; Siti Afiqah Zainuddin; Siti Alawiah Siraj; Hawa Ahmad @ Abdul Mutalib (2014)
The study is to examine the factors that may influence waqf creations in Malaysia. Academicinas from International Islamic University of Malaysia (IIUM) were sampled for their opinions on the three factors of reporting and disclosure of waqf information. awareness campaings, and the reputation of the waqf institutions. A simple random sampling method was useed whereby 350 out of 789 IIUM academicians were selected.Descriptive statistical analysis was conducted on both respondents and factors that may influence the waqf creation. The findings of the study depicted that annually reporting on financial and non-financial information on waqf, conducting awareness campaings using electronic and conventional methods as well as maintaining good relationship with beneficiaries and there is a lack of research on waqf creation. The identified factors have to be improved so that it may increase the level of waqf creation